The wicked widow - Williams, Beatriz (New York, NY : William Morrow & Co., an imprint of HarperCollinsPublishers, 2021)
"June 1925. Audacious Appalachian flapper Geneva "Gin" Kelly prepares to trade her high-flying ways for respectable marriage to Oliver Anson Marshall, a steadfast Prohibition agent who happens to hail from one of New York's most distinguished families. But just as wedding bells chime, the head of the notorious East Coast rum-running racket -- and Anson's mortal enemy -- turns up murdered at a society funeral, and their short-lived honeymoon bliss goes up in a spectacular blaze that sends Anson back undercover." --
Keywords: Socialites -- Fiction; Nineteen twenties -- Fiction; Murder -- Fiction; Man-woman relationships -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction; Romance fiction; Historical fiction